Correlating ultrasound findings of carpal tunnel syndrome with nerve conduction studies. Issue 6 (11th September 2013) - Kim, Jae Min; Kim, Min Wook; Ko, Young Jin
ABSTRACT Introduction: The aim of this study was to make correlations between ultrasonographic measurements of thenar muscle and flexor retinaculum and nerve conduction studies (NCS) in carpal tunnel syndrome (CTS). Methods: Ultrasound and NCS were performed on 92 wrists with CTS and on 40 wrists from healthy individuals. Ultrasound of thenar and hypothenar muscles, flexor retinaculum, and median nerve were assessed. The ultrasonographic findings were compared between the 2 groups, and correlation analyses between median latency and ultrasonographic findings were performed. Results: Motor latency correlated positively with flexor retinaculum thickness (FRT) and negatively with the ratio of thenar to hypothenar muscle. FRT and motor latency were found to be increased significantly in CTS. The ratio of thenar to hypothenar muscle was found to be decreased significantly in CTS compared with controls. Conclusions: The ultrasonographic findings of FRT and thenar muscle reflect the severity of disease in patients with CTS and are valuable for the diagnosis of CTS. Muscle Nerve48: 905–910, 2013